1987
DOI: 10.1111/j.1432-1033.1987.tb11011.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence of autophagic protein degradation in isolated rat hepatocytes

Abstract: The effect of small changes in intracellular ATP on autophagic flux was studied in isolated rat hepatocytes by using inhibitors of ATP production or by varying the metabolic conditions. The following observations were made.1. There was a linear relationship between endogenous protein degradation and intracellular ATP, the rate of proteolysis declining with decreasing ATP concentrations. 15% of the maximal proteolysis is either independent of ATP or has a very high affinity for this metabolite.2. There was a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 42 publications
6
65
0
2
Order By: Relevance
“…3F). We have previously shown that proteolysis in hepatocytes is quite sensitive to inhibition by relatively small decreases in intracellular ATP concentration, a 25% fall in intracellular ATP resulting in 20% inhibition of proteolysis [26]. It can be concluded, therefore, that a small part of the inhibition of proteolysis by high concentrations of added amino acids under our experimental conditions was due to the fall in ATP concentration.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…3F). We have previously shown that proteolysis in hepatocytes is quite sensitive to inhibition by relatively small decreases in intracellular ATP concentration, a 25% fall in intracellular ATP resulting in 20% inhibition of proteolysis [26]. It can be concluded, therefore, that a small part of the inhibition of proteolysis by high concentrations of added amino acids under our experimental conditions was due to the fall in ATP concentration.…”
Section: Discussionmentioning
confidence: 64%
“…Since autophagic proteolysis is dependent on ATP and sensitive to relatively small changes in intracellular ATP concentration [26], this parameter was also measured as a function of medium osmolarity. The intracellular level of ATP slightly increased with decreasing osmolarity and was unaffected by the presence of amino acids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, exposure of perfused liver to hyperosmotic media (from 305 to 385 mosmol kg-') resulted in a 22 +2 % (n = 6) stimulation of branched-chain amino acid (leucine plus valine plus isoleucine) release from 168 + 5 to 203 + 7 nmol/min per g (n = 6), owing to a 15-26% increase in the release of the individual amino acids. Because branched-chain amino acids are neither synthesized nor catabolized in rat liver [16], their release into effluent perfusate of isolated perfused rat liver can be used as an estimate of the proteolytic rate [2][3][4]6,7]. The possibility that the decreased leucine release is explained by an inhibition of leucine transport out of the cell during hypo-osmotic cell swelling is very unlikely, because steady-state release rates are reached, and restoring normo-osmotic perfusion conditions is not followed by an overshoot in leucine release, as one might expect when leucine would accumulate intracellularly during hypo-osmotic cell swelling.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids such as glutamine are known to be potent inhibitors of proteolysis in rat liver; however, the underlying mechanism is not understood [1][2][3][4][5][6][7]. Recent studies have indicated that amino acids, even at physiological concentrations [8], elicit liver cell swelling and volume-regulatory ion-flux responses [8-1 1].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Defects in ATP synthesis, which might be due to failure in energy homeostasis, occurs at an early stage of necrosis, while a certain level of ATP synthesis can still be maintained until the late stages of apoptosis and autophagy. [21][22][23][24] Results from our lab revealed that axonal ATP levels start to decrease while the AMP level increases at early stages of Wallerian degeneration. 25 These observations further support the idea that mechanisms of axon degeneration might share more similarities with the mechanisms of necrosis than with those of apoptosis or autophagic cell death.…”
Section: Axon Degeneration and Cell Deathmentioning
confidence: 96%